Analyzing the Economic Viability and Benefits of Solar Energy Implementation in Hargeisa, Somalia - Arab, Abdikarim; Nur Syafiqah Adha Narrudin; BIN RAZALI, MOHD AZAHARI (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Solar energy (SE) is a very significant and widely embraced form of renewable energy technology. Solar energy is intricately connected to other kinds of renewable energy, including wind energy, hydropower, and bioenergy. The capacity to produce electricity and heat directly from solar energy is expanding as scientific and technological advancements progress. The project has selected a crystalline silicon solar panel for its supporting case study in Hargeisa, Somalia. This study focuses exclusively on the areas of design and cost analysis. These dependencies have contradictory impacts on the agricultural sector. The noteworthy discoveries from the exploration offer valuable understanding into off-grid photovoltaic technology that could be appropriate for the given places. This study aims to assess the feasibility of solar electricity in Somalia and ascertain the costs involved with the installation of solar panels in individual residences. Energy, especially electricity, is an essential necessity for modern civilization. However, due to the limited supply of fossil fuels and the increasing global demand caused by population growth and economic expansion, it is crucial to implement appropriate measures to prevent potential disasters for nations and the planet. Homer Software is being utilized to optimize the creation of a self-contained solar home system in Hargeisa, Somalia. This system will consist of a 25kW photovoltaic (PV) capacity and will include battery backup. The objective of this study was to analyze solar radiation data, ascertain the daily load requirement, dimension the PV array and inverter, and model the system using Homer software.